The Use of Culture, Molecular Methods and Whole Genome Sequencing to Detect the Source of an Outbreak of Legionnaire's Disease in New York State. (March 2022) - Wroblewski, D.; Saylors, A.; Haas, W.; Cummings, K.; Cukrovany, A.; Connors, J.; Thompson, L.; Dickinson, M.; Baker, D.; Morse, M.; Smith, G.; Dziewulski, D.; et al.
Abstract : Purpose: Legionnaire's disease (LD) is a systemic infection caused predominantly by Legionella pneumophila (Lp). Symptoms include fever, cough, headache, body aches and shortness of breath. Legionella pneumophila serogroup 1 (Lp1) is the main serogroup responsible for outbreaks in the United States. In August 2019, a community-associated outbreak of LD was identified in a New York county including 17 cases of Lp1. During this outbreak investigation, potential environmental sources within a 5-mile radius were tested. By using a combination of culture, molecular methods, and whole-genome sequencing (WGS) the Wadsworth Center laboratory (WC) was able to identify the outbreak source. Methods & Materials: WC utilizes a streamlined testing algorithm that combines molecular screening of primary specimens followed by culture on PCR-positive samples. DNA was extracted from clinical and environmental samples using a manual procedure. Following the extraction, a multiplex real-time PCR was performed to detect Lp, Lp1 and other Legionella species. Samples that were positive for Lp1 were directly plated on BCYE, blood agar (TSA with sheep blood) and simultaneously set up using the IDEXX Legiolert™ method. Colonies typical of Lp1 were confirmed by real-time PCR and subjected to WGS and analysis using the in-house developed Legionella clustering (LegioCluster) pipeline to determine isolate relatedness. Results: In total, 53 specimens were tested between August 2019 and December 2019, including 36 environmental samples (cooling towers, fountains, wastewater) and 17 patient specimens. Lp1 DNA was detected in 8 patient specimens and Lp1 was cultured from 6 of 8 specimens. Lp1 was detected and isolated from 4 environmental samples. The IDEXX method was essential in the isolation of Lp1 from 2 clinical and 2 environmental samples. WGS analysis results demonstrated that 4 of the clinical isolates were closely related to each other and to an environmental sample (2-5 SNP differences). All other environmental isolates were not related. Conclusion: The efficient testing algorithm used by WC was instrumental in the isolation of Lp1 in this investigation. The combined use of molecular methods, various culture techniques including the IDEXX platform, and WGS analysis confirmed the source of the outbreak, helping to prevent any further cases.